US Policies Increase Vulnerability of Immigrant Communities to the COVID-19 Pandemic - Fernando A. Wilson; Jim P. Stimpson (Annals of Global Health, 2020)
The adverse policy environment in the United States (US) has made immigrant communities particularly vulnerable to uncontrolled community spread of COVID-19. Past and recent federal and state policy actions may exacerbate undetected community spread in immigrant communities and commensurate economic impact. Given the importance of immigrants to the US economy and society, and the human toll this pandemic is having on migrants worldwide, federal and state policies should pivot to find ways to improve access to healthcare for immigrants.